The feminization of agriculture in post-Soviet Tajikistan - Nozilakhon Mukhamedova; Kai Wegerich (Journal of Rural Studies, 2018)
In this paper we aim to analyse economic and social transition factors affecting the agricultural labor force and to understand the feminization phenomenon in rural Tajikistan. Agrarian reforms, seasonal male labor outmigration, and the subsequent increase in women's labor participation have facilitated changes in gender occupational segregation. We assume that in post-Soviet transition countries such as Tajikistan, the process of feminization grew from the need to take on jobs and to to slip in the role of the breadwinner due to the absence of men. The process enabled women to gain knowledge and experience in new employment positions. We contribute to the knowledge on feminization by conducting qualitative, case based analysis through in-depth interviews and focus group discussions and present unique data on previously unobserved employment categories and their characteristics from the Sughd province of Tajikistan. Results suggest that existing local systems of power and male-dominated relationships are being challenged due to male labor force outmigration, leading to a feminization of the remaining labor force and recipient clients. The jobs women perform remain subject to low protection, security, and earnings. However, increased participation in the labor force provides a gateway to a wider spectrum of labor opportunities and advances women's roles in primary agricultural production as well as in the service supply sector, and provides them a certain amount of control over their own lives.
Keywords: 330; Gender; Post-Soviet agriculture; Feminization; Farm and water management; Service providers; Central Asia